EVALUATION OF NAA LABORATORY RESULTS IN INTER-COMPARISON ON DETERMINATION OF TRACE ELEMENTS IN FOOD AND ENVIRONMENTAL SAMPLES - Diah Dwiana Lestiani; Syukria Kurniawati; Natalia Adventini (GANENDRA Majalah IPTEK Nuklir, 2012)
Inter-comparison program is a good tool for improving quality and to enhance the accuracy and precision of theanalytical techniques. By participating in this program, laboratories could demonstrate their capability andensuring the quality of analysis results generated by analytical laboratories. The Neutron Activation Analysis(NAA) laboratory at National Nuclear Energy Agency of Indonesia (BATAN), Nuclear Technology Center forMaterials and Radiometry-PTNBR laboratory participated in inter-comparison tests organized by NAA workinggroup. Inter-comparison BATAN 2009 was the third inter-laboratory analysis test within that project. Theparticipating laboratories were asked to analyze for trace elements using neutron activation analysis as theprimary technique. Three materials were distributed to the participants representing foodstuff, and environmentalmaterial samples. Samples were irradiated in rabbit facility of G.A. Siwabessy reactor with neutron flux ~ 1013n.cm-2.s-1, and counted with HPGe detector of gamma spectrometry. Several trace elements in these sampleswere detected. The accuracy and precision evaluation based on International Atomic Energy Agency (IAEA)criteria was applied. In this paper the PTNBR NAA laboratory results is evaluated.Keywords: inter-comparison, neutron activation analysis, trace elements, foodstuff, environmental samples,NAA laboratory